PENGARUH MOTIVASI, KOMPENSASI , DAN KOMPETENSI TERHADAP KINERJA PENDAMPING PROGRAM KELUARGA HARAPAN DI SUMATERA SELATAN - Afrilliana, Nadia (MOTIVASI, 2016)
Purpose - The purpose of this research was to determine the effect of motivation, compensation, competency to the Family Hope Program Assistants Performance Selatan.Design/methodology - Respondents in this study there are 262 Companion. Samples were 150 samples with a cluster sampling technique.Findings – The author finds that all of the variables as motivation, compensation, competency significantly effect on performance companion variable in South Sumatra.